2013
DOI: 10.5430/jnep.v3n8p170
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between student peer and faculty evaluations of clinical performance: A pilot study

Abstract: Background: Student peer evaluation is widely used as a form of formative or summative evaluation in a variety of classroom settings; however, the utilization of peer evaluation is not well reported in the nursing literature as part of the clinical evaluation process. Purpose: The purpose of this pilot study was to examine relationships between student peer and faculty evaluations of clinical performance in a baccalaureate nursing program. Participants consisted of clinical faculty (n = 2) and their nursing st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 20 publications
0
9
0
7
Order By: Relevance
“…Çalışmadan elde edilen bir diğer bulgu ise öz ile eğitici değerlendirme ve akran ile eğitici değerlendirme puan ortalamaları arasında anlamlı bir fark olduğudur. Bu sonuç, öz ile eğitici değerlendirme 2,11,25 ve akran ile eğitici değerlendirmenin 4,11 incelendiği çalışma sonuçlarıyla benzerdir. Ayrıca, çalışmada öz değerlendirme ile akran değerlendirme arasında anlamlı bir fark bulunmuştur.…”
Section: Tartişma Ve Sonuçunclassified
See 1 more Smart Citation
“…Çalışmadan elde edilen bir diğer bulgu ise öz ile eğitici değerlendirme ve akran ile eğitici değerlendirme puan ortalamaları arasında anlamlı bir fark olduğudur. Bu sonuç, öz ile eğitici değerlendirme 2,11,25 ve akran ile eğitici değerlendirmenin 4,11 incelendiği çalışma sonuçlarıyla benzerdir. Ayrıca, çalışmada öz değerlendirme ile akran değerlendirme arasında anlamlı bir fark bulunmuştur.…”
Section: Tartişma Ve Sonuçunclassified
“…1,2 Genel olarak klinik değerlendirmede kullanılan eğitici değerlendirme daha önceden belirlenmiş değerlendirme araçları ile gözlem yoluyla yapılmaktadır. 2,3,4 Gelenekselleşmiş olan bu yöntemin kullanımında objektif olamama, eşitsizlik, bias gibi sorunlar ortaya çıkabilmektedir. 4 Literatürde klinik değerlendirme konusunda sıkıntı yaşandığı, yeterlilik tanımlarının açık olmadığı, objektif ölçümlerin yapılamadığı, değerlendirme konusunda öğrenci bilgisinin yetersiz olduğu ve öğrencinin değerlendirme aşamasında aktif olmadığı belirtilmektedir.…”
unclassified
“…Despite these efforts, students remained relatively unsatisfied with the instructors’ ability to motivate students to evaluate their own performance. This may be due to the fact that such modes of instruction are still considered novel, and students’ perceptions and attitudes towards group discussion need to change [7]. …”
Section: Preceptors’ Feedback Provision Skillsmentioning
confidence: 99%
“…Thus, the value of peer evaluation in undergraduate clinical nursing programs needs to be emphasized as it helps nursing students to be aware about their own strengths and weaknesses as compared with their peer and reinforces their learning objectives in clinical settings. [1] Similarly, McDonald and Boud (2003) [36] reported that the skill of self assessment must be developed in high school students through training as it has a positive effect on the students achievement as well as overall performance.…”
Section: Nursing Students' Peer Evaluation Performancementioning
confidence: 99%
“…[1] Nursing students should take an active role in their learning process. Therefore, faculty educators should use different active learning strategies such as case studies, pair shares, role-playing, debate, cooperative learning and peer evaluation.…”
Section: Introductionmentioning
confidence: 99%